Teknologi Tepat Guna Sel Surya Untuk Penerangan Kolam Di Dusun I Timur Karang Anyar Sumatera Utara - Lubis, M. Arif Fadhillah; Akhiruddin, Akhiruddin; Kamil, Idham (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2022)
Dusun I Timur is one of the hamlets located in Karang Anyar Village, Beringin District, Deli Serdang Regency, North Sumatra, located close to Pantai Labu with a distance of 49.3 km from the Politeknik Negeri Medan campus. who operates a fish pond where the fish that are raised are koi fish, Mr. Putra Kurniawan, a service partner admitted that he has been working on this koi fish pond for more than 10 years with 3 ponds owned by each measuring 10 chains, often partners have to carry out their activities at night to sort the fish according to their size in each pond, because the partner's pond is quite far from the electricity network, partners are only assisted with makeshift lighting from a flashlight, besides that without adequate pond lighting at night the security level fish ponds are also not good where they are prone to theft as well as wild animals editors who come looking for food into the pond at harvest time, this service is intended to provide a solution to the problem of lighting partners' fish ponds at night by utilizing solar energy using solar panels.